The role of antifreeze glycoprotein (AFGP) and polyvinyl alcohol/polyglycerol (X/Z-1000) as ice modulators during partial freezing of rat livers - Tessier, Shannon N.; Haque, Omar; Pendexter, Casie A.; Cronin, Stephanie E. J.; Hafiz, Ehab O. A.; Weng, Lindong; Yeh, Heidi; Markmann, James F.; Taylor, Michael J.; Fahy, Gregory M.; Toner, Mehmet; Uygun, Korkut (Frontiers in Physics, 2022)
Introduction: The current liver organ shortage has pushed the field of transplantation to develop new methods to prolong the preservation time of livers from the current clinical standard of static cold storage. Our approach, termed partial freezing, aims to induce a thermodynamically stable frozen state at high subzero storage temperatures (−10°C to −15°C), while simultaneously maintaining a sufficient unfrozen fraction to limit ice-mediated injury. Methods and results: Using glycerol as the main permeating cryoprotectant agent, this research first demonstrated that partially frozen rat livers showed similar outcomes after thawing from either −10°C or −15°C with respect to subnormothermic machine perfusion metrics. Next, we assessed the effect of adding ice modulators, including antifreeze glycoprotein (AFGP) or a polyvinyl alcohol/polyglycerol combination (X/Z-1000), on the viability and structural integrity of partially frozen rat livers compared to glycerol-only control livers. Results showed that AFGP livers had high levels of ATP and the least edema but suffered from significant endothelial cell damage. X/Z-1000 livers had the highest levels of ATP and energy charge (EC) but also demonstrated endothelial damage and post-thaw edema. Glycerol-only control livers exhibited the least DNA damage on Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining but also had the lowest levels of ATP and EC. Discussion: Further research is necessary to optimize the ideal ice modulator cocktail for our partial-freezing protocol. Modifications to cryoprotective agent (CPA) combinations, including testing additional ice modulators, can help improve the viability of these partially frozen organs.